2015
DOI: 10.1007/s13762-015-0887-x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and fate of metals in urban wastewater treatment plants: a review

Abstract: The concerns on metals in urban wastewater treatment plants (WWTPs) are mainly related to its contents in discharges to environment, namely in the final effluent and in the sludge produced. In the near future, more restrictive limits will be imposed to final effluents, due to the recent guidelines of the European Water Framework Directive (EUWFD). Concerning the sludge, at least seven metals (Cd, Cr, Cu, Hg, Ni, Pb and Zn) have been regulated in different countries, four of which were classified by EUWFD as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 60 publications
1
36
1
1
Order By: Relevance
“…257) [ 8 ], whereas in the European Union (EU), to which Poland belongs, in the Council Directive of 12 June 1986 (86/278/EEC) [ 20 ]. However, it must be emphasized that processes commonly used in municipal WWTPs do not guarantee definite heavy metal removal [ 21 ]. So, application of sewage sludge to land solves the problem of its final disposal, but on the other hand may pose the potential risk associated with the secondary contamination of soil and ground water by heavy metals present in the sludge [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…257) [ 8 ], whereas in the European Union (EU), to which Poland belongs, in the Council Directive of 12 June 1986 (86/278/EEC) [ 20 ]. However, it must be emphasized that processes commonly used in municipal WWTPs do not guarantee definite heavy metal removal [ 21 ]. So, application of sewage sludge to land solves the problem of its final disposal, but on the other hand may pose the potential risk associated with the secondary contamination of soil and ground water by heavy metals present in the sludge [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This increases freshwater scarcity worldwide, since the contaminated water may cause human diseases due to the wide variety of viruses, bacteria, and protozoa, these waters may contain. Apart from these biological contaminants, the wastewater effluents are also polluted with chemicals, e.g., nitrogen, phosphorus, heavy metals [2], and organic compounds [3,4] among which detergents, pesticides, hydrocarbons, and metabolites. Wastewater effluents rich in decomposable organic matter are the primary cause of organic pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater effluents rich in decomposable organic matter are the primary cause of organic pollution. Most heavy metals present in the water are associated with industrial discharges but are also found in the wastewater treatment plants’ (WWTP) effluents [2]. Therefore, the management and utilization of natural resources need to be further improved, and human pollution activities to be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the average removal ratios range from 20% to 97% for As, 10% to 79% for Cd, 33% to 98% for Hg, 50% to 77% for Cr, and 30% to 96% for Pb. This is attributed to the fact that MWTPs are not designed for removing heavy metals, and the apparent removal in most of the cases is the result of the metals partitioning to the solid phase of the treatment systems [52]. Thus, the release of heavy metals from MWTPs into the environment should not be ignored.…”
Section: Removal Ratiosmentioning
confidence: 99%